2005
DOI: 10.1523/jneurosci.0968-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Primate Thalamus Is a Key Target for Brain Dopamine

Abstract: The thalamus relays information to the cerebral cortex from subcortical centers or other cortices; in addition, it projects to the striatum and amygdala. The thalamic relay function is subject to modulation, so the flow of information to the target regions may change depending on behavioral demands. Modulation of thalamic relay by dopamine is not currently acknowledged, perhaps because dopamine innervation is reportedly scant in the rodent thalamus. We show that dopaminergic axons profusely target the human an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
187
2
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(207 citation statements)
references
References 48 publications
11
187
2
1
Order By: Relevance
“…These observations, when put in the context of the extra GABAergic and dopaminergic modulatory inputs noted in the introduction (Barthó et al, 2002;Bokor et al, 2005;Sanchez-Gonzalez et al, 2005), suggest that higher order nuclei may have modulatory effects not observed in first order nuclei. This, in turn, suggest that modulation of corticocortical processing through thalamus (i.e.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…These observations, when put in the context of the extra GABAergic and dopaminergic modulatory inputs noted in the introduction (Barthó et al, 2002;Bokor et al, 2005;Sanchez-Gonzalez et al, 2005), suggest that higher order nuclei may have modulatory effects not observed in first order nuclei. This, in turn, suggest that modulation of corticocortical processing through thalamus (i.e.…”
Section: Discussionmentioning
confidence: 83%
“…There are several subcortical, presumably modulatory, sources that tend to innervate higher order rather than first order nuclei. These include GABAergic inputs from the anterior pretectal nucleus and zona incerta (Barthó et al, 2002;Bokor et al, 2005) and dopaminergic inputs from an as yet undefined source (Sanchez-Gonzalez et al, 2005). There is also evidence for a difference in the postsynaptic effects of cholinergic inputs to thalamic relay cells (Mooney et al, 2004;Varela and Sherman, 2004): in first order nuclei, these are depolarizing, but in higher order nuclei, these are hyperpolarizing for a substantial minority of relay cells.…”
Section: Other Differences Between First Order and Higher Order Thalamentioning
confidence: 99%
See 1 more Smart Citation
“…DAT-IR has been reported in thalamus (Melchitzky and Lewis, 2001) and thalamic [ 11 C]cocaine accumulation was proposed to reflect DAT binding (Telang et al, 1999). Moreover, a very recent report described a significant dopaminergic innervation of the primate thalamus including a confirmation of widespread DAT-IR localization (Sanchez-Gonzalez et al, 2005). Thus, thalamic [ 11 C]altropane accumulation may reflect DAT-binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Though DAT are found in both brain regions the concentration in cerebellum is low (Glaser et al, 2006;Sanchez-Gonzalez et al, 2005). However, DA regulation of metabolism in these brain regions could be indirect via striato-thalamic or striato-cerebellar pathways (Hoshi et al, 2005).…”
Section: Dat −/− Mice Have Significantly Greater Baseline Bglum Than mentioning
confidence: 99%